The role of knowledge, awareness and environmental attitudes in green product management - C. Candrianto; H. Aimon; S.U. Sentosa (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Manager involvement is very important in environmental protection. Since then, many managers have integrated environmental sustainability into their business strategies by adopting green practices that focus on green products. The aim of the current study is to examine the effect of environmental knowledge on green products and the mediating role of environmental awareness and environmentally friendly attitudesMETHODS: This study used a structured questionnaire for collecting data, where respondents were asked to provide their responses to green products produced by environmentally friendly manufacturing companies. The partial least squares structural equation modeling was used to test and analyze the relationships in the proposed model.FINDINGS: The results of the study explained that in order to create a green product, managers'' awareness of the environment needs to be formed which can be realized by the presence of a number of knowledge about the environment. Thus, environmental awareness is a mediator between environmental knowledge and green products. However, an environmentally friendly attitude is not a mediator between environmental knowledge and green products.CONCLUSION: Managers'' awareness of the environment must be realized by sharing knowledge about the importance of protecting the environment because this will affect the production of green products.